Questionnaire survey on methods of determining the relationship of the mandibular canal and third molars - Mainali, Apeksha; Vaidya, A (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Clinicians should assess and monitor mandibular canal (MC) to achieve an uneventful and successful final result. Two dimensional techniques like panoramic radiography, intra oral periapical radiographs are commonly used for assessment of MC, along with three dimensional techniques like cone beam computed tomography (CBCT). Objectives: To assess the radiologic modalities and assessment criteria used by clinically practicing dental surgeons when determining the proximity of MC to third molars. Method: A questionnaire based study was carried out among national and international oral maxillofacial surgeons and general dental practitioners. Data were fed to SPSS software version 21 for descriptive statistics. Result: Most of the participants (54.7%) in the study preferred combination of panoramic radiograph and CBCT for determining the relationship of mandibular canal and third molars measures. Conclusion: Initial screening can be carried out using panoramic radiograph which is a popular method in determining the relation between the third molar and mandibular canal in spite of some limitations. Cone Beam Computed Tomography is an important three-dimensional imaging technique which is a preferred method amongst most dental surgeons. Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page: 44-50